(3GSJYGfI GdeJge HeMGe ai bGfhf GdELQGAGJ GdLfGFjI GddjHi h GdeUQi (B: s (3OQGSI ebGQfI (B/ s - (3UGdM QeVGf UGdM bfGf s; (3TQja SjO cGeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3JfGhdJ gPg GdOQGSI GSJYGfI GdeJge HeMGe aj bGfhf GdELQGAGJ GdLfGFjI GddjHj h GdeUQj aj cd eQGMd GdOYhi GdLfGFjI(B: (3GHJOGA ef eQMdI LeY GdGSJOdGdGJ eQhQB HeQMdI GdJMbjb GdGHJOGFi hUhdB Edi eQMdI GdeMGceI h bO JHjf dfG HCf GdeTQY GddjHj h GdeUQj de jfUG Ydi Mb GdeJge aj GdGSJYGfI HeMGe aj eQMdI LeY GdGSJOdGdGJ HfUhU UQjMI(B: (3ceG Cf GdeTQY GddjHj de jfU Ydi GdVeGfGJ GdcGajI dMb GdeJge aj GdGSJYGfI HeMGe aj eQMdI GdJMbjb GdGHJOGFi h eQMdI GdeMGceI(B: (3h NGUI YfOeG jchf GdeJge MOKB Ch eJgeB HLfMI eYGbHB YdjgG HGdMHS hLhHB QZe EfTGDg dLgGR GdeMGeGI GdTYHjI GdPj jYWi ddeJge GdMb aj GddLhA Edjg ddMUhd Ydi NOeGJ eMGe HOhf ebGHds
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2011s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B231-254s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GSJYGfI GdeJge HeMGe aj bGfhf GdELQGAGJ GdLfGFjI s; (3Mb GdGWdGYs; (3GdeTQY GddjHj h GdeUQi s; (3GdGSJLhGHs; (3GdWdHGJ hGdOahYs; (3eMGce Cef GdOhdIs; (3Mbhb GdOaGYs; (3MeGjI GdeJge ef NjGfI hcjdgs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs